So this is related to the Cookbook and I tried solving it maybe two decades ago, gave up, and was reminded of the unsolved problem. But it's pretty damn straight forward, but I still got slogged down in the muck.
This is a simple Bandpass filter (BPF) with resonant frequency Ω0 and resonance Q:
H(s)=1QsΩ0(sΩ0)2+1QsΩ0+1
At the resonant frequency
|H(jΩ)|≤H(jΩ0)=1
and the upper and lower bandedges are defined so that
|H(jΩU)|2=|H(jΩ02BW/2)|2=12
|H(jΩL)|2=|H(jΩ02−BW/2)|2=12
We call these the "half-power bandedges". Because we're audio, we define bandwidth in octaves, and in the analog world this bandwidth in octaves, BW, is related to Q as:
1Q=2BW−1√2BW=2sinh(ln(2)2BW)
We're using bilinear transform (with pre-warped resonant frequency) which maps:
sΩ0←1tan(ω0/2)1−z−11+z−1jΩΩ0←jtan(ω/2)tan(ω0/2)
letting z=ejω and s=jΩ.
The resonant angular frequency of the analog filter is Ω0, and with frequency warping compensation done to the resonant frequency in the realized digital filter, when ω=ω0 (the user-defined resonant frequency), then Ω=Ω0.
So if analog angular frequency is
ΩΩ0=tan(ω/2)tan(ω0/2)
then it's mapped to the digital angular frequency as
ω=2arctan(ΩΩ0tan(ω0/2))
Now, the upper and lower bandedges in the analog world are
ΩU=Ω02BW/2 ΩL=Ω02−BW/2
and in digital frequency domain are
ωU=2arctan(ΩUΩ0tan(ω0/2))=2arctan(2BW/2tan(ω0/2))
ωL=2arctan(ΩLΩ0tan(ω0/2))=2arctan(2−BW/2tan(ω0/2))
Then the actual difference, in log frequency of the bandeges (which is the actual bandwidth in the digital filter) is:
bw=log2(ωU)−log2(ωL)=log2(2arctan(2BW/2tan(ω0/2)))−log2(2arctan(2−BW/2tan(ω0/2)))
or
ln(2)bw=ln(arctan(eln(2)BW/2tan(ω0/2)))−ln(arctan(e−ln(2)BW/2tan(ω0/2)))
This has a functional form of
f(x)=ln(arctan(αex))−ln(arctan(αe−x))
where f(x)≜, x \triangleq \frac{\ln(2)}{2}BW and \alpha \triangleq \tan(\omega_0/2)
What I want to do is invert f(x) (but I know I can't do it exactly with a nice closed form). I have already done a first-order approximation and i want to bump it up to a third-order approximation. And this has become a sorta copulating female canine, even though it should be straight forward.
Now this has something to do with the Lagrange Inversion Formula and I only want to take it to one more term than I have.
We know from above that f(x) is an odd-symmetry function:
f(-x) = -f(x)
This means f(0)=0 and all even-order terms of the Maclaurin series will be zero:
y = f(x) = a_1 x + a_3 x^3 + ...
The inverse function is also odd symmetry, goes through zero, and can be expressed as a Maclaurin series
x = g(y) = b_1 y + b_3 y^3 + ...
and if we know what a_1 and a_3 are of f(x), then we have a good idea what b_1 and b_3 must be:
b_1=\frac{1}{a_1} \quad \quad \quad \quad b_3 = -\frac{a_3}{a_1^4}
Now, I am able to calculate the derivative of f(x) and evaluate it at zero and i get
\\ a_1 = \frac{2 \alpha}{(1+\alpha^2) \arctan(\alpha)} = \frac{\sin(\omega_0)}{\omega_0/2} \\ b_1 = \frac{(1+\alpha^2) \arctan(\alpha)}{2 \alpha} = \frac{\omega_0/2}{\sin(\omega_0)} \\
But I am having a bitch of a time getting a_3 and therefore b_3. Can someone do this? I'd even settle for a solid expression for the third derivative of f(x) evaluated at x=0.
Answer
okay, i promised to put up bounty and i will keep my promise. but i have to confess that i might renege a little bit on being satisfied with just the third derivative of f(x). what i really want are the two coefficients for g(y).
so i didn't realize that there was this Wolfram language as an alternative to mathematica or Derive and i didn't realize it could so easily compute the third derivative and simplify the expression.
and this Markus guy at the math SE posted this answer (which i thought was gonna have to be the amount of grunge i thought would be needed).
\begin{align*} y = f(x) &= \ln\left(\arctan\left(\alpha e^x\right)\right) - \ln\left(\arctan\left(\alpha e^{-x}\right)\right)\\ \\ &\approx a_1 x \ + \ a_3 x^3 \\ \\ &=\frac{2\alpha}{(1+\alpha^2)\arctan(\alpha)} x + \frac{\alpha}{3(1+\alpha^2)^3\arctan(\alpha)}\Bigg(\alpha^4-6\alpha^2+1\\ &\qquad\left.-\frac{3\alpha(1-\alpha^2)}{\arctan(\alpha)}+\frac{2\alpha^2}{\left(\arctan(\alpha)\right)^2}\right) x^3 \\ \\ \end{align*}
so i put together the third-order approximation to the inverse:
\begin{align*} x = g(y) &\approx b_1 y \ + \ b_3 y^3 \\ \\ &= \frac{1}{a_1} y \ - \ \frac{a_3}{a_1^4} y^3 \\ \\ &= \frac{(1+\alpha^2)\arctan(\alpha)}{2\alpha} y - \frac{(1+\alpha^2)(\arctan(\alpha))^3}{48 \alpha^3}\Bigg(\alpha^4-6\alpha^2+1 \\ &\qquad\left.-\frac{3\alpha(1-\alpha^2)}{\arctan(\alpha)}+\frac{2\alpha^2}{\left(\arctan(\alpha)\right)^2}\right) y^3 \\ \\ &= \frac{(1+\alpha^2)\arctan(\alpha)}{2\alpha} y - \frac{(1+\alpha^2)(\arctan(\alpha))^3}{48 \alpha}\Bigg(\alpha^2-6+\alpha^{-2} \\ &\qquad\left.-\frac{3(1-\alpha^2)}{\alpha\arctan(\alpha)}+\frac{2}{\left(\arctan(\alpha)\right)^2}\right) y^3 \\ \\ &= y \left(\arctan(\alpha)\frac{\alpha + \alpha^{-1}}{2}\right) \Bigg(1 \ + \\ & \left((\arctan(\alpha))^2\left(1-\frac{\alpha^2+\alpha^{-2}}{6} \right) - \arctan(\alpha)\frac{\alpha-\alpha^{-1}}{2}-\frac{1}{3}\right) \frac{y^2}{4} \Bigg) \\ \\ \end{align*}
i was kinda hoping someone else would do this. recall y=f(x) \triangleq \ln(2) \, bw, g(y) = x \triangleq \frac{\ln(2)}{2}BW and \alpha \triangleq \tan(\omega_0/2)
\begin{align*} x = g(y) &\approx y \left(\arctan(\alpha)\frac{\alpha + \alpha^{-1}}{2}\right) \Bigg(1 \ + \\ & \left((\arctan(\alpha))^2\left(1-\frac{\alpha^2+\alpha^{-2}}{6} \right) - \arctan(\alpha)\frac{\alpha-\alpha^{-1}}{2}-\frac{1}{3}\right) \frac{y^2}{4} \Bigg) \\ \\ \frac{\ln(2)}{2}BW &\approx (\ln(2) bw) \left(\arctan(\alpha)\frac{\alpha + \alpha^{-1}}{2}\right) \Bigg(1 \ + \\ & \left((\arctan(\alpha))^2\left(1-\frac{\alpha^2+\alpha^{-2}}{6} \right) - \arctan(\alpha)\frac{\alpha-\alpha^{-1}}{2}-\frac{1}{3}\right) \frac{(\ln(2) bw)^2}{4} \Bigg) \\ \\ \end{align*}
i have three convenient trig identities:
\frac12 \left(\alpha + \alpha^{-1} \right) = \frac12 \left(\tan(\omega_0/2) + \frac{1}{\tan(\omega_0/2)} \right) = \frac{1}{\sin(\omega_0)} \\
\frac12 \left(\alpha - \alpha^{-1} \right) = \frac12 \left(\tan(\omega_0/2) - \frac{1}{\tan(\omega_0/2)} \right) = -\frac{1}{\tan(\omega_0)} \\
\frac12 \left(\alpha^2 + \alpha^{-2} \right) = \frac12 \left(\tan^2(\omega_0/2) + \frac{1}{\tan^2(\omega_0/2)} \right) = \frac{1}{\sin^2(\omega_0)} + \frac{1}{\tan^2(\omega_0)} \\ = \frac{2}{\sin^2(\omega_0)} - 1
"finally" we got:
BW \approx bw \, \frac{\omega_0}{\sin(\omega_0)} \left(1 \ + \ \frac{(\ln(2))^2}{24} \left( 2(\omega_0^2 - 1) - \left(\frac{\omega_0}{\sin(\omega_0)}\right)^2 + 3\frac{\omega_0}{\tan(\omega_0)} \right) (bw)^2 \right)
this ain't so bad. fits on a single line. if someone sees an error or a good way to simplify further, please lemme know.
with the power series approximation from the comment above,
BW \approx bw \, \frac{\omega_0}{\sin(\omega_0)} \left(1 \ + \ (\ln(2))^2 \left( \tfrac{1}{36}\omega_0^2 - \tfrac{1}{180}\omega_0^4 - \tfrac{2}{2835}\omega_0^6 \right) (bw)^2 \right)
No comments:
Post a Comment